Do Tissues From THA Revision of Highly Crosslinked UHMWPE Liners Contain Wear Debris and Associated Inflammation? - Baxter, Ryan M. (Springer-Verlag, 2010)
BACKGROUND: Polyethylene wear debris is a major contributor to inflammation and the development of implant loosening, a leading cause of THA revisions. To reduce wear debris, highly crosslinked ultrahigh-molecular-weight polyethylene (UHMWPE) was introduced to improve wear properties of bearing surfaces. As highly crosslinked UHMWPE revision tissues are only now becoming available, it is possible to examine the presence and association of wear debris with inflammation in early implant loosening. QUESTIONS/PURPOSES: We asked: (1) Does the presence of UHMWPE wear debris in THA revision tissues correlate with innate and/or adaptive immune cell numbers? (2) Does the immune cell response differ between conventional and highly crosslinked UHMWPE cohorts? METHODS: We collected tissue samples from revision surgery of nine conventional and nine highly crosslinked UHMWPE liners. Polarized light microscopy was used to determine 0.5- to 2-μm UHMWPE particle number/mm(2), and immunohistochemistry was performed to determine macrophage, T cell, and neutrophil number/mm(2). RESULTS: For the conventional cohort, correlations were observed between wear debris and the magnitude of individual patient macrophage (ρ = 0.70) and T cell responses (ρ = 0.71) and between numbers of macrophages and T cells (ρ = 0.77) in periprosthetic tissues. In comparison, the highly crosslinked UHMWPE cohort showed a correlation between wear debris and the magnitude of macrophage responses (ρ = 0.57) and between macrophage and T cell numbers (ρ = 0.68). Although macrophages and T cells were present in both cohorts, the highly crosslinked UHMWPE cohort had lower numbers, which may be associated with shorter implantation times. CONCLUSIONS: The presence of wear debris and inflammation in highly crosslinked UHMWPE revision tissues may contribute to early implant loosening.